2023
DOI: 10.3390/su15054631
|View full text |Cite
|
Sign up to set email alerts
|

Urban Functional Zone Classification Based on POI Data and Machine Learning

Abstract: The identification of urban spatial functional units is of great significance in urban planning, construction, management, and services. Conventional field surveys are labour-intensive and time-consuming, while the abundant data available via the internet provide a new way to identify urban spatial functions. A major issue is in determining point of interest (POI) weights in urban functional zone identification using POI data. Along these lines, this work proposed a recognition method based on POI data combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…For result verification, 353 sample blocks were selected as the test set for identification verification, and then compared with Google satellite images and Baidu maps [12] . The number of correctly identified cells was judged by visual interpretation, and the results showed that the number of correctly identified grid cells was 302, with an overall accuracy of 85.55% (Table 4).…”
Section: Results Verification and Functional Area Classification Displaymentioning
confidence: 99%
“…For result verification, 353 sample blocks were selected as the test set for identification verification, and then compared with Google satellite images and Baidu maps [12] . The number of correctly identified cells was judged by visual interpretation, and the results showed that the number of correctly identified grid cells was 302, with an overall accuracy of 85.55% (Table 4).…”
Section: Results Verification and Functional Area Classification Displaymentioning
confidence: 99%
“…The accuracy rate and recall rate are used as evaluation metrics, and are calculated using Formulas ( 15) and ( 16), respectively. F1 values are used to combine the accuracy and recall rates according to Formula (17).…”
Section: Evaluation Of the Building Function Identification Resultsmentioning
confidence: 99%
“…The arrival of the geographic big data era has brought massive online geographic information resources, such as social perception data from social media [13], cab trajectory data [14], cell phone data [15], street-view image data [16], and point of interest (POI) data [17,18]. These record a large amount of information about human activities and have been widely used in the study of urban spatial structure characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Qian et al applied hierarchical cluster method to study the spatial distribution and structure of urban functions in 200 Chinese cities on different time scales [29]. Luo et al identified a relationship diagram of POI data and classification of urban spatial functions, calculated the densities of each type of POI, and used the density values of various POIs in the research unit as feature vectors to recognize urban spatial function by the Kstar algorithm [30].…”
Section: Urban Functionmentioning
confidence: 99%